Linking digital capability to small business performance: the mediating role of digital business transformation - Yudha Prakasa; Zulfiqar Ali Jumani (Cogent Business & Management, 2024)
This study investigates the impact of digital capability (DC) on digital business transformation (DBT), and its effect on small business performance (BP). This study adopts a quantitative approach. The theoretical framework uses knowledge-based view (KBV) and dynamic capability theories. This study empirically examines the direct relationship between DT and DBT in small business performance (financial, flexibility, and quality performance). This study involved 330 small businesses in East Java, Indonesia, using a convenience sampling technique. This hypothesis was tested using structural equation modeling. The findings showed a significant effect of DC on DBT and BP, DBT, and BP. Thus, the results provide evidence that DBT plays a mediating role between DC and BP. This study makes three contributions to the literature. First, empirical evidence supports the KBV and dynamic capability theories that knowledge is the most valuable asset in the digital age. Second, this study significantly extends the relevant literature by highlighting the relationship between DC, DBT, and BP. Finally, this study proposes a multiple-dimension small business performance model that uses three dimensions (financial, flexibility, and quality) as the determinant factors of DC and DBT in the SMEs sector.
Keywords: 650; Digital Capability (DC); Digital Business Transformation (DBT); Small Business Performance (BP); Knowledge-Based View (KBV); Structural Equation Modeling (SEM)